2014
DOI: 10.1097/shk.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyltransferase Inhibitor, Tipifarnib, Prevents Galactosamine/Lipopolysaccharide-Induced Acute Liver Failure

Abstract: Acute liver failure (ALF) is a fatal syndrome associated with massive hepatocyte death. There is no cure for ALF except liver transplantation. Protein farnesylation is a lipid modification of cysteine residues that is catalyzed by farnesyltransferase (FTase) and has been proposed as an integral component of acute inflammation. Previously, we have demonstrated that FTase inhibitors improve survival in mouse models of endotoxemia and sepsis. Here we studied the effects of FTase inhibitor, tipifarnib, on galactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Low doses of LPS in combination with the specific hepatotoxic agent D-galactosamine (GalN) promote specific liver injury in mice and induce the production of inflammatory cytokines (TNF-α, IL1B and IL-6) 39 thus recapitulating the clinical picture of acute liver injury in humans 39 . For these reasons, the LPS/GalN-induced hepatic injury is a widely used mouse model to understand fulminant hepatitis and its pharmacological treatment 3941 . Because the clock machinery controls the circadian behavior of the immune system, we hypothesized that the outcome of fulminant hepatitis may depend on the time of hepatitis induction.…”
Section: Resultsmentioning
confidence: 99%
“…Low doses of LPS in combination with the specific hepatotoxic agent D-galactosamine (GalN) promote specific liver injury in mice and induce the production of inflammatory cytokines (TNF-α, IL1B and IL-6) 39 thus recapitulating the clinical picture of acute liver injury in humans 39 . For these reasons, the LPS/GalN-induced hepatic injury is a widely used mouse model to understand fulminant hepatitis and its pharmacological treatment 3941 . Because the clock machinery controls the circadian behavior of the immune system, we hypothesized that the outcome of fulminant hepatitis may depend on the time of hepatitis induction.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 2 major mechanisms of cell death, namely the death receptor pathway and the mitochondrial pathway, are involved in the progression of alF, in which TnF serves a crucial role (25). The caspase family is a key contributor to cell apoptosis, and it has been reported that caspase-3 is significantly activated in the ALF model (26). in addition, apoptotic-associated proteins tightly control cell apoptosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Tipifarnib (2) prevented protein farnesylation in the liver and markedly attenuated liver injury and mortality in galactosamine (GalN)-lipopolysaccharide (LPS)challenged mice by inhibiting GalN-LPS-induced caspase 3 activation, inflammatory cytokine production and c-Jun N-terminal kinase (JNK) phosphorylation in the liver, upregulating anti-apoptotic protein Bcl-xL, and protecting primary hepatocytes from GalN/tumor necrosis factor-α (TNF-α)induced cell death. 126…”
Section: Other Diseasesmentioning
confidence: 99%